2009
DOI: 10.1016/j.virol.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of c-Kit expression and activation in KSHV-infected endothelial cells

Abstract: Kaposi’s sarcoma (KS) herpesvirus (KSHV) is the etiological agent of several immunodeficiency-linked cancers, including KS. Our previous work showed that the proto-oncogene c-kit is upregulated in KSHV-infected endothelial cells (EC), as well as in KS lesions. We show here that KSHV-dependent induction of both c-kit mRNA and protein requires the establishment of a latent infection and that this upregulation occurs in primary DMVEC as well as in immortalized DMVEC (eDMVEC). Interestingly, we find that while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Previous work demonstrated CD117 expression in vitro on latently infected dermal ECs (43,54) and on cells present in large numbers in KS lesions, with 93% of CD117 + lesions LANA + (55). Clinical trials testing the efficacy of Gleevec/imatinib mesylate in the treatment of KS showed promise, with demonstrated clinical and histological regression of cutaneous KS lesions (56).…”
Section: Resultsmentioning
confidence: 95%
“…Previous work demonstrated CD117 expression in vitro on latently infected dermal ECs (43,54) and on cells present in large numbers in KS lesions, with 93% of CD117 + lesions LANA + (55). Clinical trials testing the efficacy of Gleevec/imatinib mesylate in the treatment of KS showed promise, with demonstrated clinical and histological regression of cutaneous KS lesions (56).…”
Section: Resultsmentioning
confidence: 95%
“…NCT00090987) and achieved a partial regression of cutaneous KS lesions in some patients (57,58). Inhibition of c-kit and/or platelet-derived growth factor (PDGF) receptors by imatinib may have contributed to this observation (59,60). However, imatinib does not inhibit the tyrosine kinase function of KSHV ORF21/TK ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…102,124,[133][134][135][136] These experiments support the classification of KSHV as a bona fide human tumor virus; however, tissue culture systems, by design, are finely tuned to respond to pro-growth signals with drastic changes in cell pheno-…”
mentioning
confidence: 68%
“…The KSHV miRNAs in isolation also induce trans‐differentiation and hallmarks of transformation 76,78,97,98,131,132 . In culture, KSHV can transform both endothelial and mesenchymal lineage precursors, as well as experimental cell models, to the point that they form tumors as xenografts in immune‐deficient mice 102,124,133–136 . These experiments support the classification of KSHV as a bona fide human tumor virus; however, tissue culture systems, by design, are finely tuned to respond to pro‐growth signals with drastic changes in cell phenotypes.…”
Section: The Lineage Of the Ks Tumor Cellmentioning
confidence: 81%